Channel resolution enhancement through scalability of nano/micro-scale thickness and width of SU-8 polymer based optical channels using UV lithography - Amiri, Iraj Sadegh; Sorger, Volker J.; Ariannejad, Mohammad Mahdi; Ling, Xi; Ghasemi, M.; Yupapin, Preecha Promphan (Springer Verlag (Germany), 2018)
This paper reports on an approach for fabrication of micro-channels with nanometer thickness achieved by optimization of UV lithography processes. Rectangular micro-channels with a staple edge are fabricated over the surface of a silicon wafer substrate in which a sub-micron layer of diluted SU-8 thin film has been coated. The optimization of the process parameters includes the duration of a two-step pre- and post-baking process, UV exposure dosage, and finally chemical developing time with constant agitation. This produces recipe produces micro-channels with high contrast edges and thickness below 100 nm. The dimensions achieved using this approach has potential applications in sub-micron optical waveguides and nanoelectromechanical (NEMS) devices.